Digital Transformation and Financial Report Accountability: A Study of MSMEs Post-Pandemic in Indonesia - Diana Magfiroh (Journal of Taxation Insights Policy Practice, 2025)
Digital transformation has become inevitable for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia following the COVID-19 pandemic. However, the adoption of digital technology by MSMEs has not been fully followed by increased accountability in financial reporting. This study aims to analyze the extent to which digital transformation has influenced MSME financial reporting practices and to identify inhibiting factors and strategies for improving technology-based financial accountability. This study used a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and questionnaires distributed to MSME actors and administrative staff in DKI Jakarta, West Java, and Central Java. The results show that the majority of MSMEs have adopted digital technology for recording transactions and sales but have not yet integrated these systems into standardized financial reporting practices. The main obstacles include low digital accounting literacy, limited time and resources, and the absence of direct incentives from the government or financial institutions. The most effective strategies for improving accountability are through practice-based training, community mentoring, and integrating digital reporting with access to financing. This study concludes that digital transformation has the potential to strengthen MSME financial accountability if supported by policy interventions and human resource capacity building.